Implementasi Jump Diffusion Untuk Memprediksi Harga Saham Serta Analisis Risiko Menggunakan Value At Risk Dan Expected Shortfall (Studi Kasus: PT. Indofood Sukses Makmur Tbk) - Feby Seru; Miftachul Jannah; Tiku Tandiangnga (Department of Mathematics, Hasanuddin University, 2024)
Stock prices often fluctuate; therefore, a model is needed to predict the stock price. One of the models that can be used to predict stock prices when experiencing a jump is Jump Diffusion. In addition to predicting, investment is inseparable from the risks that may be borne, so it is also necessary to measure risk. This study aims to implement the Jump Diffusion Model in predicting the stock price of PT Indofood Sukses Makmur Tbk and conduct a risk analysis of the prediction results using Value at Risk (VaR) and Expected Shortfall (ES). In this study, a model was obtained that was used to predict the share price of PT Indofood Sukses Makmur Tbk with a Mean Absolute Percentage Error (MAPE) value of 6.41%. This shows that the accuracy of the stock price prediction results is included in the very good category. In addition, the VaR value of the prediction results with a confidence level of 90%, 95%, and 99% is 0.0292, 0.0372, and 0.0523, and the ES value is 0.0402, 0.0474, and 0.0613.